Development of a reliable UHPLC-MS/MS method for simultaneous determination of zearalenone and zearalenone-14-glucoside in various feed products - Zhang, Zhiqi; Cai, Yaling; Fan, Kai; Huang, Qingwen; Zhao, Xiuying; Cao, Haojie; Zhao, Zhihui; Tangni, Emmanuel K.; Han, Zheng (Frontiers in Chemistry, 2022)
A reliable ultra-high-performance liquid chromatography–tandem mass spectrometry method (UHPLC-MS/MS) was developed for the simultaneous determination of two mycotoxins, that is, zearalenone (ZEN) and zearalenone-14-glucoside (ZEN-14G) in formula feed, concentrated feed, and premixed feed products. An improved sample pretreatment was achieved with the hydrophilic–lipophilic balance (HLB) cartridges efficiently removing the impurities and enriching the target analytes in different feeds. The critical parameters affecting the performance of the solid-phase extraction (SPE) procedure were carefully optimized, and 20% acetonitrile in water as the loading solution, 50% methanol in water as the washing solvent, and 5 ml of methanol as the elution solvent yielded the optimal purification efficiencies. The established method was thoroughly validated in terms of linearity (R2 ≥ 0.999), sensitivity (limit of quantification in the range of 0.50–5.00 μg kg−1), recovery (89.35 ± 2.67% to 110.93 ± 1.56%), and precision (RSD, 3.00–14.20%), and it was then successfully applied to investigate a total of 60 feed samples. Among them, 50 samples were found to be contaminated with ZEN (an incidence of 83.3%) at levels ranging from 0.63 to 615.24 μg kg−1, whereas 22 samples were contaminated with ZEN-14G (an incidence of 36.7%) in the range of 0.89–15.31 μg kg−1. The developed method proved to be a specific and reliable tool for intensive monitoring of ZEN and ZEN-14G in complex feed matrices.